Time of Onset of Necrotizing Enterocolitis and Focal Perforation in Preterm Infants: Impact on Clinical, Surgical, and Histological Features - Berrington, Janet Elizabeth; Embleton, Nicholas David (Frontiers in Pediatrics, 2021)
Objective: There is no gold standard test for diagnosis of necrotising enterocolitis (NEC). Timing of onset is used in some definitions and studies in an attempt to separate NEC from focal intestinal perforation (FIP), with 14 days used as a cut-off. In a large detailed dataset we aimed to compare NEC and FIP in preterm infants born <32 weeks gestation, presenting before 14 days of life in comparison to cases presenting later. Design: Infants with NEC or FIP where parents had consented to enrolment in an observational and sample collection study were included from 2009 - 2019. Clinical, surgical, histological and outcome data were extracted and reviewed by each author independently. Patients/episodes: In 785 infants 174 episodes of NEC or FIP were identified of which 73 (42%) occurred before 14 days including 54 laparotomies, and 19 episodes of medically managed NEC (‘early’). There were 56 laparotomies and 45 episodes of medically managed NEC presenting on or after 14 days age (‘late’). Results: In early cases 41% of laparotomies were for NEC (22 cases) and 59% for FIP (32 cases), and in late cases 91% of laparotomies (51 cases) were for NEC and 9% (5 cases) were for FIP. NEC presenting early was more likely to present with an initial septic presentation, rather than discrete abdominal pathology, and less likely to have clear pneumatosis. Early cases did not otherwise differ clinically, surgically or histologically or in outcomes compared to later cases. FIP features did not differ by age at presentation. Conclusions: Whilst most FIP occurred early, 14% occurred later whereas almost one-third (29%) of NEC cases (surgical and medical) presented early. Infant demographics, surgical and histological findings of early and late presenting disease did not differ, suggesting that early and late cases are not necessarily different subtypes of the same disease, although a common pathway of different pathogenesis cannot be excluded. Timing of onset will not accurately distinguish NEC from FIP and caution should be exercised in including timing of onset in diagnostic criteria.